Addressing the safety trilemma: a safe sovereign asset for the eurozone - Ad van Riet (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
At the 25th anniversary of the Maastricht Treaty, this paper reviews the merits of introducing a safe sovereign asset for the eurozone. The triple euro area crisis showed the costly consequences of ignoring the "safety trilemma". Keeping a national safe sovereign asset (the German bund) as the cornerstone of the financial system is incompatible with having free capital mobility and maintaining economic and financial stability in a monetary union. The euro area needs a single safe sovereign asset. However, eurobonds are only foreseen after full fiscal integration. To address the safety trilemma member countries must therefore act as the joint sovereign behind the euro and choose from two options. First, they could establish a credible multipolar system of safe national sovereign assets. For this purpose, they could all issue both senior and junior tranches of each national government bond in a proportion such that the expected safety of the senior tranche is the same across countries while the junior tranche would absorb any sovereign default risk. Additional issuance of national GDP-linked bonds could insure governments against a deep recession that might lead to a self-fulfilling default and thereby help to make the junior tranche less risky. The second option is that the member countries together produce a common safe sovereign asset for a truly integrated and stable monetary union by creating synthetic eurobonds comprising both a safe senior claim and a risky junior claim on a diversified portfolio of national government bonds. This appears a more effective solution to the safety trilemma - especially when euro area governments would also issue national GDP-linked bonds - but it requires flanking measures to control for moral hazard.
Keywords: F33; F34; G15; H63; H7; 330; safety trilemma; capital mobility; safe sovereign asset; synthetic eurobonds